(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Education is the key to success in the life of an individual. According to scholar’s, thinkers and educationists like Mahatma Gandhi, Swami vivekanad, Johan Devey etc, education is is modification of behavior, prepares a man for life, removes darkness from life of every individual, the manifestation of perfection already in men, process of experience and socialization etc. In short we can say that education is multi functionary in the life of an individual. A teacher according to our thinkers ,educationists in past posses pivotal around which all the teaching learning process revolves and also he/she develops all round personality of children’s. But when a teacher having all the facilities and healthy salary from the government becomes irresponsible it leads in falling tower of education. Government is providing all facilities to their teacher’s to raise the stander of education in the schools where all the children’s of poor people’s are looking for their bright career but due to ignorance of irresponsible teacher’s their career is in danger. Today we are living in 21st centaury having lass with science and technological tools we can analyses major fall in the result as well as enrollment in these government schools from primary to secondary level. When these children’s reaches in colleges and universities for higher studies we can analyses lack of absolute knowledge of reading and writing as average or dull. Due to this reason of carelessness of government school teacher’s poor parents are trying to send their children’s in private schools instead of government schools for their secure and better future. Even some government teacher’s are also sending their children’s in private schools. On the basis of above lines we can say this decline in the education system especially in govt. schools in large scale. All these facts presented in this paper abstract are on the basis of personal experience and primary survey. All the above facts presented in these lines is due to the wrong criteria of selection of teachers, lack of proper teacher training, and less eligibility of teachers.